IMPACT OF ADDING AJWAIN SEEDS TO THE MALE LAMBS’ RATIONS AS GROWTH PROMOTERS - S. El-Naggar; S. Gad; Z. Mahasneh; M. Tawilla; G Abou-Ward (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to investigate the impact of adding ajwain seeds to the rations of the growing Ossimi ram lambs on growth performance, nutrient digestibility, rumen liquor fermentation, and blood biochemical parameters. A total of 15 ram lambs, 5-6 months of age, were randomly allocated to the 3 treatments (5 lambs each). Lambs were fed a basal diet and regarded as a control group (T1), while the second (T2) and third (T3) treatments were fed on a basal diet plus 0.2 and 0.4 % of ajwain seeds respectively. At the end of the trial (150 days), three sheep from each treatment were used for a fourteen-day digestibility trial. Feed intake was similar for all groups. The treated groups exhibited higher (P<0.05) average daily gain and lesser (P<0.05) feed conversion ratio than the T1 group. All nutrients digestibility and nutritive value (TDN and DCP) were significantly higher (P<0.05) in the T2 and T3 groups than in the T1 group. The blood attributes were within the reference values of healthy lambs. Serum cholesterol, triglyceride, LDL, and MDA levels were decreased (P<0.05), whereas, albumin, HDL and TAC concentrations increased in the treated than the control groups. I<n conclusion, adding ajwain seed (0.2 and 0.4%) to the ram lambs’ ration can enhance the animal health and promote the growth performance.